A Novel Poly(N‐Isopropylacrylamide‐co‐acryloylamidobenzo‐12‐crown‐4) Microgel with Rapid Stimuli‐Responsiveness for Molecule‐Specific Adsorption of γ‐Cyclodextrin. Issue 20 (13th July 2017) - Wei, Yun‐Yan; Liu, Zhuang; Luo, Feng; Zhang, Lei; Wang, Wei; Ju, Xiao‐Jie; Xie, Rui; Chu, Liang‐Yin
Abstract: A novel poly( N ‐isopropylacrylamide‐ co ‐acryloylamidobenzo‐12‐crown‐4) (PNB) microgel with rapid γ‐cyclodextrin (CD)‐responsive characteristics and adsorption property is developed. The microgel is composed of benzo‐12‐crown‐4 (B12 C4 ) units as molecule‐recognition receptors and poly( N ‐isopropylacrylamide) networks as phase‐transition actuators as well as adsorbent backbone chains. The PNB microgels significantly increase their volumes induced by γ‐CD, and adsorb γ‐CD molecules within PNB networks because of formation of γ‐CD/B12 C4 inclusion complexes. Detection of γ‐CD‐concentration and the molecule‐specific adsorption processes of the microgels are investigated systematically. The PNB microgels provide a new tool for rapid concentration measurement and effective separation of γ‐CD. Abstract : A novel poly( N ‐isopropylacrylamide‐ co ‐acryloylamidobenzo‐12‐crown‐4) (PNB) microgel with rapid γ‐cyclodextrin (CD)‐responsive characteristics and adsorption property is developed. The PNB microgels significantly increase their volumes induced by γ‐CD, and adsorb γ‐CD molecules within PNB networks because of formation of γ‐CD/B12 C4 inclusion complexes. Detection of γ‐CD‐concentration and the molecule‐specific adsorption processes of the microgels are investigated systematically.